Muscle mass and physical function in patients with bladder cancer—Data from a prematurely terminated prospective cohort study - Omland, Lise Høj; Ammitzbøll, Gunn; Lund, Cecilia Margareta; Lindberg, Henriette; Dalton, Susanne Oksbjerg; Suetta, Charlotte; Pappot, Helle (Frontiers in Rehabilitation Sciences, 2022)
Background Patients with bladder cancer (BC) have a high prevalence of comorbidity and low adherence to systemic anticancer treatment but it is unknown whether this is associated with sarcopenia. Objective We aimed to investigate if the sarcopenia defining parameters muscle strength, muscle mass and physical performance were associated with reduced adherence to systemic anticancer treatment in patients with BC, and if these muscle domains changed during treatment. Methods Patients >18 years of age with BC referred for chemotherapy or immunotherapy at Department of Oncology, Rigshospitalet, Denmark were eligible for study inclusion. Measurements were performed before treatment initiation and within one week after treatment termination, and consisted of assessments of muscle strength, muscle mass, and physical performance. Data was compared with thresholds outlined by the European Working Group on Sarcopenia in Older Patient’s (EWGSOP2) guidelines and a healthy, age-matched Danish cohort. Results Over a period of 29 months, we included 14 patients of whom two completed follow-up measurements. The recruitment rate was <50% of planned, mainly due to logistics and Covid-19 related limitations. Consequently, a decision to prematurely terminate the study was made. No patients fulfilled EWGSOP2 criteria for sarcopenia, but the majority had reduction in one or more muscle domains when compared to healthy, age-matched individuals. Most patients had dose reductions or treatment postponements. Conclusions In this prematurely terminated study, no patients fulfilled EWGSOP2 criteria for sarcopenia, yet, most patients were affected in one or more muscle domains and the majority had compromised treatment adherence.